Peruvian poet and playwright Sebastián Salazar Bondy reading from his poetry - Salazar Bondy, Sebastián; Library of Congress (Washington DC, USA) (1958)
Mr. Salazar Bondy reads fifteen poems from his collected volumes, Conducta sentimental and Confidencia en alta voz.
From Confidencia en alta voz: Confidencia el alta voz (min. 00:03); El poeta conoce la poesía (min. 01:55); Costa y mujer (min. 03:24); Elogio de la carne (min. 06:17); Remordimiento en alguna calle (min. 07:37); El domingo (min. 13:58); Confidencia (Cita en el bullicio) (min. 14:58); Tres valces criollos (min. 16:00); Los amigos (min. 19:15); Pueblo español (min. 20:20); Desde el corazón (min. 21:41); Sueño del extranjero (min. 22:47); Como una religión (min. 22:07); El sol de España (Adios en Santander) (min. 25:10) -- From Conducta sentimental: Todo esto es mi país (min. 08:54).
Recorded Sept. 15, 1958, USIS, Lima.
Archive of Hisp. Lit. on Tape
Preservation master.
Also available in digital form on the Library of Congress Web site.
Keywords: Poetry